Elements of critical discourse in copywriting on Malaysian celebrity television advertisement - Roslan, Nur Widad; Abdul Halim, Hazlina; Abdul Jabar, Mohd Azidan; Mamat, Roslina (Canadian Center of Science and Education, 2019)
This study focuses on the elements of critical discourse in copywriting on Malaysian celebrity television advertisements. The objectives of this study is to identify and discuss the elements of critical discourse in copywriting on Malaysian celebrity television advertisement videos. This study will focus on the textual analysis, one of the three dimensions of Fairclough’s (1995) critical discourse analysis. The data is analyzed by using the qualitative method. 10 Malaysian celebrity television advertisements copy were chosen as samples for this study. Results from this study have helped in the process of identifying the presence of the textual analysis sub categories which are grammar, theme, metaphor, repetition and conjunction. Therefore, it is hoped that further studies will be focus on the use of appropriate textual analysis in future advertisement copies.